2018
DOI: 10.20510/ukjpb/6/i1/173524
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Mycochemical and Proximate Composition of Oyster Mushrooms (Pleurotus ostreatus VAR Florida, (MONT) Singer. and P. pulmonarius (FR) QUEL) Grown on Bark of Gmelina arborea Roxb., Straw of Saccharum officinarum L. and Pods of Delonix regia

Abstract: Mushrooms are fungal fruit-bodies which have over successive years served as suitable source of protein, carbohydrates, minerals and vitamins. The fruit-bodies derive their nutrients from varieties of substrates including agro-wastes. This study was conducted to evaluate the potentials of using the pods of Delonix regia, straws of Saccharum officinarum and bark of Gmelina arborea in the production of nutritionally-rich edible oyster mushrooms, Pleurotus ostreatus and Pleurotus pulmonarius. The experiment was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Saponin was reduced in 'Ogiri', a locally made condiment from castor seeds (CSF), while CPF has the highest concentration. Research carried out by Okwulehie et al (2018) revealed that Pleurotus ostreatus has a higher content of saponin, which could have led to the high saponin content of CPF. The reduction observed in CSF may be as a result of long boiling time and fermentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saponin was reduced in 'Ogiri', a locally made condiment from castor seeds (CSF), while CPF has the highest concentration. Research carried out by Okwulehie et al (2018) revealed that Pleurotus ostreatus has a higher content of saponin, which could have led to the high saponin content of CPF. The reduction observed in CSF may be as a result of long boiling time and fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…Fermented castor seeds (CPF and CSF) had higher alkaloid content than the raw castor seeds. Research carried out by Okwulehie et al (2018) revealed that Pleurotus ostreatus has high alkaloid content, which may probably be responsible for the increase alkaloid concentration of CPF.…”
Section: Discussionmentioning
confidence: 99%